Childhood Violence, High School Academic Environment, and Adult Alcohol Use Among Latinas and Black Women: A Structural Equation Modeling Study - Capasso, Ariadna (Journal of interpersonal violence, 2024)
Objective:Young Latinas and Black women drink less than women of other racial/ethnic groups but experience more alcohol-related problems in midlife. This study aims to identify modifiable factors to prevent adult onset of alcohol use disorder (AUD) in this population.Methods:Data were collected at six time points as part of the Harlem Longitudinal Development Study from 365 Latinas (47%) and Black (53%) women (mean age at time 1 = 14, standard deviation 1.3). Structural equation modeling was used to test hypothesized pathways from childhood physical and sexual abuse to AUD via depressive mood, anxiety disorders, and somatic complaints in the 20s. We also tested the moderation effect of the high school academic environment by including in the structural equation model two latent variable interaction terms between the school environment and each of the abuse variables.Results:Childhood physical and sexual abuse was positively associated with depressive mood, anxiety disorders, and somatic complaints when participants were in the 20s. Depressive mood mediated childhood abuse and AUD when women were in the 30s. The high school academic environment attenuated the effect of physical, but not sexual abuse, on depressive mood (β = −0.59, B = −9.38, 95% CI [−14.00, −4.76]), anxiety symptoms (β = −0.61, B = −14.19, 95% CI [−21.76, −6.61]), appetite loss (β = −0.41, B = −10.52, 95% CI [−15.61, −5.42]), and sleeplessness (β = −0.50, B = −9.56, 95% CI [−13.95, −5.17]) in the early 20s.Conclusions:Our findings underscore the need to invest in early violence prevention interventions and in education to ensure equitable access to quality, academically oriented, and safe schools.